Ferrite Nanoadsorbents for Heavy Metal Removal: Research Evolution, Adsorption Mechanisms, and Future Challenges - Meiliyadi, Lalu Ahmad Didik; Rahman, Muh. Zainur; Jamiluddin, Jamiluddin; Arizona, Kurniawan; Febriana, Nadia; Damayanti, Isniwana (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2026)
Ferrite nanoadsorbents have attracted increasing attention for heavy metal remediation because of their magnetic separability, high adsorption capacity, and potential reusability. This review provides a comprehensive synthesis of research developments by integrating bibliometric mapping with an analysis of adsorption mechanisms and emerging research challenges. A bibliometric literature review was conducted using Scopus-indexed publications published between 2011 and 2025. After a systematic screening process, relevant research articles were analyzed to identify publication trends, collaboration networks, leading journals, research hotspots, and thematic evolution. The findings reveal sustained growth in research activity, with contributions concentrated in high-impact journals and strong international collaboration led primarily by Asian countries. Keyword mapping indicates that research has evolved from fundamental heavy metal removal studies toward mechanistic investigations of adsorption processes and, more recently, to the development of advanced ferrite-based nanocomposites emphasizing recyclability, stability, and environmentally sustainable water treatment. Mechanistic analysis further shows that adsorption performance is governed by the synergistic effects of surface functional groups, pore structure, adsorption kinetics, and magnetic recovery. Despite substantial progress, challenges remain regarding nanoparticle agglomeration, regeneration efficiency, long-term environmental safety, and large-scale commercialization. This review provides an integrated understanding of the evolution of ferrite nanoadsorbent research while identifying critical knowledge gaps and future research priorities to support the development of efficient, sustainable, and practically applicable water remediation technologies.